Applicability of Blood Pressure–Lowering Drug Trials to Real-World Patients With Cardiovascular Disease. Issue 2 (February 2021) - Bonekamp, Nadia E.; Spiering, Wilko; Nathoe, Hendrik M.; Kappelle, L. Jaap; de Borst, Gert J.; Visseren, Frank L.J.; Westerink, Jan
Abstract : This study aimed to assess applicability of blood pressure–lowering drug trials to real-world secondary preventive care. We applied the eligibility criteria of the landmark blood pressure–lowering drug trials (EUROPA, PEACE, HOPE-peripheral arterial disease [PAD], PRoFESS, and PROGRESS) to patients with coronary artery disease (CAD; n=5155), peripheral arterial disease (PAD; n=1487), and cerebrovascular disease (n=2515) participating in the UCC-SMART cohort. Baseline differences according to trial eligibility were assessed. Differences in risk of all-cause mortality and a composite of cardiovascular death, myocardial infarction, and stroke (major adverse cardiovascular event) were calculated using Cox proportional hazard models, adjusted for age, sex, and cardiovascular risk factors. Seventy-five percent of UCC-SMART patients with CAD would have been eligible for EUROPA, 84% for PEACE, 59% of patients with PAD for HOPE-PAD, 17% of patients with cerebrovascular disease for PRoFESS, and 100% for PROGRESS. Eligible patients were older (average difference ranging 1.4–14.6 years across trials). Eligible patients with CAD were at lower risk of major adverse cardiovascular event after adjustment for age, sex, and cardiovascular risk factors in PEACE (hazard ratio, 0.65 [95% CI, 0.53–0.79]) and of mortality in both EUROPA (hazard ratio, 0.72 [95% CI, 0.62–0.82]) and PEACE (0.63 [95% CI, 0.51–0.78]). Adjusted mortality and major adverse cardiovascular event risks were not different between eligible and ineligible patients with PAD and cerebrovascular disease in HOPE-PAD, PRoFESS, and PROGRESS. The majority of real-world patients with CAD, PAD, or cerebrovascular disease would be eligible for landmark trials on blood pressure–lowering drugs. Patients with CAD ineligible for the EUROPA and PEACE trials are at higher adjusted mortality and major adverse cardiovascular event risks, which may limit applicability of their results to ineligible patients. Abstract : Supplemental Digital Content is available in the text.